Institutional Elements of Tax Design and Reform - McLaren, John (Washington, DC: World Bank, 2013)
This is a collection of papers that study the constraints on fiscal systems, imposed by problems of institutions, administration, and incentives in developing, and post-Socialist economies. Chapter two focuses on the administration of indirect taxation, and provides a case study of indirect taxation in Tanzania. This shows how evasion can be documented, and quantified, through a case study that looks at a particular type of reform, aimed at curbing evasion: franchising, or privatizing the right to tax, which has been tried in several Tanzanian towns as a way of collecting vendor fees, for access to a public market. Chapter three is a theoretical study of evasion under a value-added tax (VAT), and the inefficiencies it can create. Chapter four studies the fiscal constraints within the federal politics of Russia, while Chapters five and six examine case studies (India) in fiscal federalism, in which the determination of fiscal outcomes is - to a considerable degree - a matter of bargaining between political entities in the center, and in the periphery. In both cases, it appears that large-scale distortions, away from an ideal tax system, emerge as a result, suggesting corruption can be fought by increasing functional specialization within a tax bureaucracy. The last chapter looks at the problem of opportunistic taxation, particularly regarding the African context, and studies various ways in which the problem can be alleviated.